Analysis of the Prevalence Level of Sand Lobster (Panulirus homarus) in Different Shelters in Bengkulu City - Imam Barzakh; Dedi Pardiansyah; Novi Susianti; Suharun Martudi; Nasir Ahmad (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to determine the prevalence and degree of ectoparasite infection in sand lobster (Panulirus homarus) in different Tank in Bengkulu City. This study was conducted in October – November 2021 in Bengkulu City for 57 days. The method used in this study is a survey method by taking samples from a population that is being observed. Determination of the sampling location was carried out by purposive sampling method at 3 (three) locations of storage/suppliers of sand lobster in Bengkulu City. Ana Lidiana's Tank has the highest prevalence rate of 62.50%, the prevalence rate category is often.